Dexmeditomidine And Fentanyl As An Adjunct To Bupivacainein Supraclavicular Nerve Block - Dhara Darji; Neha Pareek; Bina Butala; Sagar Sanghani; Shrushti Padhiyar (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2024)
Objective: The objective of the study was to evaluate the influence of the combination of dexmedetomidine and fentanyl with bupivacaine on the efficacy of ultrasonic guided supraclavicular nerve block for upper limb surgeries. Material and Methods: The study comprised a sample of 150 patients who were scheduled to have upper limb procedures at the Department of Anaesthesia in a Tertiary Care Teaching Institute in India. A total of 150 patients were divided into three groups. Group A was administered a combination of Bupivacaine and saline, Group B received Bupivacaine along with dexmedetomidine, and Group C was given Bupivacaine in combination with fentanyl. The essential parameters of heart rate, systolic and diastolic blood pressure, and oxygen saturation were documented. Results: Both the B Group and C Group exhibited a more rapid initiation and extended duration of sensory and motor blockade, which was statistically significant (P<0.05). Group B had a longer duration of pain relief after surgery compared to Group C and Group A. Conclusion: The administration of dexmedetomidine and bupivacaine in the supraclavicular block effectively reduced the onset time of both sensory and motor blocks. Furthermore, the administration of both dexmedetomidine and bupivacaine resulted in a significant reduction of postoperative discomfort.